Challenges of treatment adherence in children with bronchial asthma - Khamzaeva Kamina (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The article analyzes factors contributing to low compliance in pediatric practice: from psychological barriers and fear of side effects (steroid phobia) to technical errors in using inhalers. Ways to improve adherence through a multidisciplinary approach and educational programs are proposed.